Institutionelle Rahmenbedingungen derAusdehnung des ökologischen Landbaus: Erfahrungen aus drei europäischen Ländern; Institutional Pre-Conditions for a Positive Development of Organic Farming in Europe - Experience from three European Countries - Susanne Padel; Johannes Michelsen (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– The paper reviews the development of the organic sector and the institutional conditions in European countries. On the basis of three case studies the interrelationship between organisations of organic and conventional agriculture in the areas of farming community, agricultural policy and food marketing is illustrated. The comparison shows that an open dialog based on mutual respect and a number of initiatives in all three areas appear to be supporting a continuous development of the organic sector.
Keywords: 330